ENHANCING CADET COMPETENCE IN AVIATION EDUCATION THROUGH A VR-BASED APPROACH LIGHTING SYSTEM - Wartoyo, Bayu Purbo; Driyono, Bambang; Suhanto, Suhanto; Ratri, Ratri; Nugrah, Andi Fadhilah; Putra, Muhammad Ridho Esha Artha (Universitas Labuhanbatu, 2025)
Purpose – The purpose of this study is to develop a Virtual Reality-based Approach Lighting System (ALS) prototype as a practicum medium for the Visual Landing Aid course in the Airport Technology Study Program at Makassar Aviation Polytechnic. This initiative aims to address the limited accessibility of ALS equipment at Sultan Hasanuddin International Airport, where the system is active and located in the restricted airside area, thereby constraining direct practicum opportunities.Methodology – The research employed a Research and Development (R&D) approach utilizing the ADDIE model consisting of five stages: (1) Analysis to identify practicum challenges, (2) Design of ALS lamp models and surrounding environment, (3) Development of the prototype using Virtual Reality applications, (4) Implementation through practicum activities, and (5) Evaluation to assess the system’s functionality and effectiveness in enhancing cadets’ learning outcomes.Findings – The study successfully produced a Virtual Reality-based Approach Lighting System Prototype that replicates the real equipment and environment. The evaluation stage demonstrated positive responses from cadets regarding the system’s effectiveness in supporting the Visual Landing Aid course. Specifically, 41.7% strongly agreed, 37.5% agreed, and 20.8% moderately agreed that the VR application improved their understanding and ability to visualize ALS concepts in a realistic context.Contribution – This research contributes to aviation education by providing a safe, innovative, and accessible practicum medium that eliminates the dependency on restricted airport environments. The VR-based ALS prototype enhances cadets’ knowledge, technical competence, and practical understanding of visual landing aids. Furthermore, the study supports the integration of Virtual Reality technology as a modern pedagogical tool in aviation training, aligning with global trends in simulation-based education.